2022
DOI: 10.1002/lio2.915
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Botox regimens in patients with adductor spasmodic dysphonia and essential tremor of voice: A 31‐year experience

Abstract: Objective The purpose of this study was to quantitatively compare the effectiveness of unilateral and bilateral botulinum toxin A (BTX‐A) injections for mitigating undesirable weak/breathy voice quality and dysphagia for patients with adductor spasmodic dysphonia and/or essential tremor of voice (ETV). Methods Data were collected from the medical records of 319 patients, yielding three treatment cohorts: patients who received an equal dose bilateral injection regimen (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Our study has some limitations. First, the included studies contained patients with both ADSD and comorbid essential vocal tremor [ 18 ]. ADSD and essential tremor both manifest as impaired neuromuscular control of the larynx.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study has some limitations. First, the included studies contained patients with both ADSD and comorbid essential vocal tremor [ 18 ]. ADSD and essential tremor both manifest as impaired neuromuscular control of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there was a general lack of subgroup analysis in the injection approach, which is problematic as the unilateral/bilateral dichotomy is overly simplistic. Some studies used alternating unilateral injections [ 12 , 18 , 19 ] versus consistent unilateral injections, warranting comparison. Other variations, including dose equality for bilateral injections [ 18 ], should also be considered for future subgroup analyses using more granular groupings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies also demonstrate that non-pharmacological factors such as education before the procedure, body position, pain, and stress sensation before btx may play a role in the effect of btx on AdSD patients [ 20 ]. In addition, a study compared unilateral and bilateral btx injections quantitatively and concluded that unilateral btx is useful for patients with an extended period with weak/breathy voice quality and those with dysphagia [ 21 ].…”
Section: Reviewmentioning
confidence: 99%